Survival of Elderly Adults Undergoing Incident Home Hemodialysis and Kidney Transplantation - Molnar, Miklos Z. (J Am Geriatr Soc, 2016)
BACKGROUND: To date, no study has compared the mortality of elderly patients with end stage renal disease (ESRD) treated with home hemodialysis (HD) versus kidney transplantation (KTx). DESIGN, SETTING, PARTICIPANTS: Using data from elderly patients (≥65 years) who started home HD and who received KTx in the US between 2007-2011, we created a 1:1 propensity score (PS)-matched cohort of 960 elderly patients and examined the association between treatment modality and all-cause mortality via Cox proportional hazard and competing risk regression survival models using modality failure as a competing event. MEASUREMENTS: modality of renal replacement therapy. RESULTS: The mean±SD age of the PS-matched home HD and KTx elderly patients at baseline were 71±6 years and 71±5 years, 69% were male (both groups), 81% and 79% of patients were white and 11% and 12% were African American, respectively. Median follow-up time was 205 days (IQR: 78-364 days) for home HD patients and 795 days (IQR: 366-1,221 days) for KTx recipients. There were 97 deaths (20%, mortality rate 253 [207-309]/1000 patient-years) in the home HD group, and 48 deaths (10%, 45 [34-60]/1000 patient-years) in the KTx group. Compared to KTx recipients, elderly patients on home HD had almost 5-times higher mortality risk (Hazard Ratio(HR): 4.74, 95% confidence interval(CI): 3.25-6.91). Similar results were seen in competing risk regression analyses (SHR: 4.71, 95%CI: 3.27-6.79). Results were consistent across different types of kidney donors and subgroups divided by various recipient characteristics. CONCLUSION: KTx is associated with greater survival than home HD in elderly patients with ESRD. Further studies are needed to assess whether KTx is also associated with other benefits such as better quality of life or lower hospitalization rates.